Multipronged Approach to Reduce Hantavirus Pulmonary Syndrome Incidence Among Rural Populations - Shrivastava, Saurabh R; Bobhate, Prateek S (National Journal of Community Medicine, 2025)
Hantavirus Pulmonary Syndrome (HPS) has been acknowledged as a public health concern, especially due to the high case fatality rate, justifying the need for promoting early detection and strengthening of preventive measures to save lives. Even though the condition is rare, it is an extremely fatal condition, with an average case fatality rate of 40%. Many rural households tend to have inadequate housing and improper storage standards for food and waste, which attract rodents and facilitate their habitation in human dwellings. Acknowledging the high case fatality rates and the presence of disease in rural populations, which are more at-risk with limited healthcare services, there is an essential need to implement targeted prevention and control measures to reduce the incidence of disease and the possibility of outbreaks. These interventions can range from rodent-proofing housing, community education campaigns, the use of personal protective equipment, etc. In conclusion, rural populations are extremely susceptible to Hantavirus Pulmonary Syndrome due to the presence of multiple predisposing factors. There arises the need to adopt a multipronged strategy, integrating education, environmental controls, and surveillance, which could substantially lower HPS burden in underserved rural areas.